Exploring Bondage-Discipline, Dominance-Submission and Sadomasochism (BDSM) - Krystian Wdowiak; Agnieszka Maciocha; Julia Wąż; Aleksandra Witas; Weronika Chachaj; Adrian Muzyka; Julia Rydzek; Ewa Gardocka (Quality in Sport)
Introduction The acronym BDSM combines terms describing various consensual sexual practices: bondage and discipline (B/D), dominance and submission (D/S), and sadism and masochism (S/M). In recent years, interest in BDSM culture has grown, both socially—likely driven by the popularity of related books and films—and academically. Purpose of the work This article aims to compile the most recent information on BDSM (bondage and discipline, dominance and submission, and sadism and masochism) based on the latest available literature. Materials and Methods The PubMed database was searched for scientific articles in which the term "BDSM" appeared in the title, abstract, or keywords. Due to the limited number of publications on this topic, the search was restricted to articles published between 2014 and 2024. Results and Conclusions The prevalence of BDSM varies widely in studies, ranging from a few percent of the population to nearly half. Studies suggest a potential link between childhood sexual abuse and a heightened interest in BDSM, particularly among women who take on submissive roles. Societal stigma and widespread misconceptions about BDSM practices continue to have a negative impact on those who engage in them. Authors emphasize the necessity of further research on BDSM practices due to the limited and sometimes contradictory findings, particularly regarding the prevalence of BDSM interest and hormonal changes resulting from these practices.